Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.dsr2.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, distribution and ecology of the order Phyllodocida (Annelida, Polychaeta) in deep-sea habitats around the Iberian margin

Abstract: The polychaetes of the order Phyllodocida (excluding Nereidiformia and Phyllodociformia incertae sedis) collected from deep-sea habitats of the Iberian margin (Bay of Biscay, Horseshoe continental rise, Gulf of Cadiz and Alboran Sea), and Atlantic seamounts (Gorringe Bank, Atlantis and Nameless) are reported herein. Thirty-six species belonging to seven families-Acoetidae, Pholoidae, Polynoidae, Sigalionidae, Glyceridae, Goniadidae and Phyllodocidae, were identified. Amended descriptions and/or new illustratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 85 publications
4
10
0
Order By: Relevance
“…Current specimens closely resemble the redescription of Eumida longicirrata ( Eibye-Jacobsen 1991 ), although the raised postero-dorsal semi-circular structures were not as distinct, and in some cases not visible at all. Similar observations were noted by Ravara et al (2017b) for E. longicirrata collected from the Gulf of Cadiz. Considering that the recorded distribution of E. longicirrata appears to be limited to the margins of the Iberian Peninsula ( Ravara et al 2017b ), we tentatively regard this as a different species until further investigation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Current specimens closely resemble the redescription of Eumida longicirrata ( Eibye-Jacobsen 1991 ), although the raised postero-dorsal semi-circular structures were not as distinct, and in some cases not visible at all. Similar observations were noted by Ravara et al (2017b) for E. longicirrata collected from the Gulf of Cadiz. Considering that the recorded distribution of E. longicirrata appears to be limited to the margins of the Iberian Peninsula ( Ravara et al 2017b ), we tentatively regard this as a different species until further investigation.…”
Section: Resultssupporting
confidence: 88%
“…Similar observations were noted by Ravara et al (2017b) for E. longicirrata collected from the Gulf of Cadiz. Considering that the recorded distribution of E. longicirrata appears to be limited to the margins of the Iberian Peninsula ( Ravara et al 2017b ), we tentatively regard this as a different species until further investigation.…”
Section: Resultssupporting
confidence: 88%
“…nov, grouped in the consensus MOTU 15 (Figure ), has an average COI distance to its congeners of 19.1%, while the unnamed Eumida GB22 lineage has 17.4% mean COI nucleotide divergence compared with the remaining Essc. These values are within the range of COI distances recorded in earlier studies between established polychaete species (Carr et al, ; Lobo et al, ; Ravara, Ramos, Teixeira, Costa, & Cunha, ). Regarding the nuclear markers, mean interspecific distance values for these two lineages are higher compared to the remaining complex (around 10.0% for ITS region and 1.5% for 28S) with the exception of E. maia and Eumida F22 (Table ), which have distances in the same range.…”
Section: Discussionsupporting
confidence: 85%
“…For example, comprehensive studies on the polychaete fauna of the Arctic ( Carr et al, 2011 ) and north-eastern Atlantic ( Lobo et al, 2016 ) reported mean COI congeneric distances (K2P) of 16.5% and 24.0%, respectively, vs the 16.9% observed here. Our findings are also consistent with pairwise comparisons among closely-related species observed both within Nereididae (e.g., Glasby, Wei & Gibb, 2013 ; Paiva et al, 2019 ) and in other polychaete families, such as Amphinomidae ( Barroso et al, 2010 ), Capitellidae ( Silva et al, 2017 ), Onuphidae ( Rodrigues et al, 2009 ; Seixas et al, 2020 ), Sabellidae ( Capa & Murray, 2015 ), Phyllodocidae ( Ravara et al, 2017 ), and Syllidae ( Álvarez-Campos, Giribet & Riesgo, 2017 ).…”
Section: Discussionsupporting
confidence: 89%